A method for oxidizing divalent iron ions using oxygen nanobubbles

By oxidizing divalent iron ions with oxygen nanobubble solution and copper catalyst under acidic conditions, the environmental and economic problems of divalent iron oxidation methods in the prior art are solved, and efficient divalent iron oxidation effect is achieved.

CN116377259BActive Publication Date: 2025-03-28NANHUA UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310418901.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-19
Publication Date
2025-03-28
Estimated Expiration
2043-04-19

AI Technical Summary

Technical Problem

Among the existing acid-induced uranium-enriched technologies, commonly used methods for divalent iron oxidation have problems such as high environmental requirements, poor adaptability, high cost, and secondary pollution.

Method used

The divalent iron ions are catalyzed with copper as a catalyst under acidic conditions.

Benefits of technology

The oxidation rate of divalent iron ions is significantly improved, and the oxidation rate can reach up to 88.51% after 24 hours, and it has the advantage of green and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116377259B_ABST
    Figure CN116377259B_ABST
Patent Text Reader

Abstract

The present invention provides a method for oxidizing divalent iron ions under acidic conditions using oxygen nanobubbles, and belongs to the technical field of uranium mining and smelting. The method comprises the following steps: (1) preparing an oxygen nanobubble solution; (2) catalytically oxidizing divalent iron ions using copper as a catalyst in the oxygen nanobubble solution obtained in step (1) under acidic conditions. The present invention uses copper as a catalyst under acidic conditions and uses oxygen nanobubbles to catalytically oxidize divalent iron ions. The results of the embodiment show that the oxidation rate of divalent iron ions after 24 hours using the method of the present invention can be as high as 88.51%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of uranium mining and smelting, and in particular relates to a method for oxidizing divalent iron ions by utilizing oxygen nanobubbles. Background Art

[0002] Acid uranium leaching technology is one of the main methods currently used in uranium mining and smelting because of its high uranium leaching rate and short leaching cycle. The uranium in uranium ore mainly exists in the form of tetravalent uranium and hexavalent uranium. Since the solubility of tetravalent uranium is extremely low, the use of oxidants to oxidize the insoluble tetravalent uranium into soluble hexavalent uranium during the acid leaching process is a prerequisite for achieving efficient leaching. Trivalent iron regenerated by ferrous iron oxidation is a commonly used oxidant for tetravalent uranium oxidation. At present, the main methods of ferrous iron oxidation are biological oxidation and chemical oxidation. Among them, biological oxidation has problems such as high environmental requirements and poor adaptability; chemical oxidation has problems such as high cost and secondary pollution.

[0003] Nanobubbles are nanoscale bubbles with a diameter of less than 1 μm that exist at the solid-liquid interface or in the solution. Compared with micron- and millimeter-sized bubbles, they have unique physical and chemical properties such as large specific surface area, long existence time, high solubility, high mass transfer efficiency, and the ability to produce strong oxidizing free radicals. These excellent physical and chemical properties also make them show broad application prospects in the fields of wastewater treatment and purification, surface cleaning, and promoting the growth of plants and animals, and are expected to replace or improve the potential of current advanced oxidation process technologies.

[0004] Therefore, introducing oxygen nanobubbles into the field of acid uranium leaching to achieve rapid and efficient oxidation of divalent iron ions to trivalent iron ions is of great significance for the efficient leaching of uranium ore. Summary of the invention

[0005] The purpose of the present invention is to provide a method for oxidizing divalent iron ions using oxygen nanobubbles. The method provided by the present invention has the advantage of being more environmentally friendly.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for oxidizing divalent iron ions using oxygen nanobubbles, comprising the following steps:

[0008] (1) preparing an oxygen nanobubble solution;

[0009] (2) catalytically oxidizing divalent iron ions using copper as a catalyst in the oxygen nanobubble solution obtained in step (1) under acidic conditions.

[0010] Preferably, the acid in the acidic condition of step (2) is one or more of sulfuric acid and hydrochloric acid.

[0011] Preferably, the pH value of the solution under acidic conditions in step (2) is 0.40-1.76.

[0012] Preferably, the copper in step (2) is copper wire or copper sheet.

[0013] The present invention provides a method for oxidizing ferrous iron using oxygen nanobubbles, comprising the following steps: (1) preparing an oxygen nanobubble solution; (2) catalytically oxidizing the ferrous iron using the oxygen nanobubble solution obtained in step (1) under acidic conditions with copper as a catalyst. The present invention uses oxygen nanobubbles to catalytically oxidize ferrous iron using copper as a catalyst under acidic conditions. The results of the embodiment show that the oxidation rate of ferrous iron after 24 hours using the method of the present invention can be as high as 88.51%. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a micrograph of oxygen nanobubbles prepared in step (1) of Example 1 of the present invention;

[0015] Figure 2 The bubble concentration and bubble size distribution diagram of the oxygen nano bubble solution prepared in step (1) of Example 1 of the present invention;

[0016] Figure 3 This is an electron spin resonance spectrum of the oxygen nanobubble solution prepared in step (1) of Example 1 of the present invention using DMPO as a spin trapping agent;

[0017] Figure 4 The oxidation effects of Comparative Examples 3 to 6 of the present invention;

[0018] Figure 5 The oxidation effects of Examples 1 to 2 of the present invention and Comparative Example 3;

[0019] Figure 6 SEM image of the copper sheet in Example 1 of the present invention;

[0020] Figure 7 This is a SEM image of the copper sheet in Comparative Example 1 of the present invention after oxidation for 24 hours;

[0021] Figure 8 This is a SEM image of the copper sheet in Example 1 of the present invention after oxidation for 24 hours;

[0022] Fig. 9 This is a SEM image of the copper wire in Example 2 of the present invention;

[0023] Fig.10 This is a SEM image of the copper wire in Comparative Example 2 of the present invention after oxidation for 24 hours;

[0024] Fig.11 This is a SEM image of the copper wire in Example 2 of the present invention after being oxidized for 24 hours;

[0025] Fig.12 This is the EDS image of the copper sheet in Example 1 of the present invention after oxidation for 24 hours;

[0026] Fig.13 This is the EDS image of the copper wire in Example 2 of the present invention after oxidation for 24 hours; DETAILED DESCRIPTION

[0027] The present invention provides a method for oxidizing divalent iron ions using oxygen nanobubbles, comprising the following steps:

[0028] (1) preparing an oxygen nanobubble solution;

[0029] (2) catalytically oxidizing divalent iron ions using copper as a catalyst in the oxygen nanobubble solution obtained in step (1) under acidic conditions.

[0030] Unless otherwise specified, the present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.

[0031] The invention prepares an oxygen nano bubble solution.

[0032] In the present invention, the method for preparing the oxygen nano bubble solution is preferably: preparing the oxygen nano bubble solution using a circulating water dynamic nano bubble generator. In the present invention, when the volume of the solution is 5 to 7L, the pressure value when preparing the oxygen nano bubble solution is preferably 4 to 6 bar, more preferably 4.5 to 5.5 bar, and most preferably 5 bar; the time when preparing the oxygen nano bubble solution is preferably 4 to 6 min, more preferably 4.5 to 5.5 min, and most preferably 5 min. The present invention limits the volume, pressure and time of the solution when preparing the oxygen nano bubble solution within the above range, which can make the oxygen nano bubbles have a smaller particle size and a higher concentration, and have better oxidation performance. In the present invention, the oxygen nano bubble generating device is preferably a Venturi generator.

[0033] In the present invention, the oxygen nano bubble solution is preferably prepared before use to avoid long-term storage that may cause the oxygen nano bubbles to burst and affect its oxidation capacity.

[0034] After obtaining the oxygen nano bubble solution, the present invention uses copper as a catalyst to catalyze oxidation of divalent iron ions in the oxygen nano bubble solution under acidic conditions.

[0035] The present invention preferably first adds a divalent iron salt and an acid into the oxygen nano bubble solution to prepare an acidic solution containing oxygen nano bubbles-divalent iron ions, and then adds copper as a catalyst for catalytic oxidation.

[0036] In the present invention, the copper preferably includes copper wire or copper sheet, more preferably copper sheet. In the present invention, the copper sheet has a larger surface area and a larger contact area with the solution, and can produce more copper ions as a catalyst, further improving the catalytic oxidation effect.

[0037] In the present invention, when the copper is a copper sheet, the volume ratio of the surface area of ​​the copper sheet to the acidic solution containing oxygen nanobubbles-divalent iron ions is preferably (20-30) cm 2 :200mL, more preferably (22-28)cm 2 :200mL, most preferably (24-26)cm 2 In the present invention, when the copper is a copper wire, the volume ratio of the copper wire to the volume of the acidic solution containing oxygen nanobubbles-divalent iron ions is preferably (0.1-0.2) cm 3 :200mL, more preferably (0.12~0.18)cm 3 :200mL, most preferably (0.14~0.16)cm 3 :200mL.

[0038] In the present invention, the concentration of divalent iron ions in the acidic solution containing oxygen nanobubbles-divalent iron ions is preferably 1-100 mg / L, more preferably 10-80 mg / L, and most preferably 0-50 mg / L. The present invention has no special limitation on the source of the divalent iron ions, and divalent iron salts well known to those skilled in the art can be used. The present invention limits the concentration of divalent iron ions within the above range, which can make the system have a better oxidation effect.

[0039] In the present invention, the acid preferably includes one or more of sulfuric acid and hydrochloric acid, more preferably sulfuric acid. In the present invention, the pH value of the acidic solution containing oxygen nanobubbles-divalent iron ions is preferably 0.40 to 1.76. The present invention limits the pH value of the acidic solution containing oxygen nanobubbles-divalent iron ions to the above range, which can better meet the actual pH conditions of acid leaching of uranium, maintain the stability of divalent iron and ferric iron, and prevent the acid concentration from being too low to produce Fe(OH)3 precipitation.

[0040] In the present invention, the temperature of the catalytic oxidation is preferably 25-35°C, more preferably 30°C; the time of the catalytic oxidation is preferably 0.1-30h, more preferably 0.5-25h. The present invention limits the temperature and time of the catalytic oxidation to the above ranges, so that the catalytic oxidation can be fully carried out.

[0041] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Example 1

[0043] (1) An oxygen nanobubble solution was prepared using a circulating water-powered nanobubble generator. The water inlet of the generator system was connected to a water pump, and untreated ultrapure water was injected into it until the entire device was filled with water (the clean water pressure was kept constant, 6.3 L). The water inlet was then closed, and the gas tank was opened to introduce compressed oxygen. The circulating pump was turned on until the pressure gauge indicated a set pressure value of 5 bar. Starting from this time, the system continued to operate until the set time of 5 min was reached, and the oxygen nanobubble solution was prepared and collected for subsequent experiments.

[0044] (2) The mother liquor of divalent iron ions is added to the oxygen nanobubble solution in proportion to obtain an oxygen nanobubble-divalent iron ion solution, sulfuric acid is immediately added to adjust the pH value and a copper sheet is added, and then the solution is placed in a constant temperature magnetic stirrer for catalytic oxidation. The solution temperature is maintained at 30° C. using a water bath, wherein the pH value of the solution is 0.40, the size of the copper sheet is 5×5 cm (the surface area of ​​the copper sheet to the volume ratio of the solution is 25 cm 2 :200mL), the initial concentration of ferrous ion in the solution is 50mg / L, the volume of solution is 200mL, and the catalytic oxidation time is 24h.When the catalytic oxidation time is 0.5h, 2h, 4h, 8h, 12h, 24h, take 2mL solution respectively to measure ferrous ion concentration.Three parallel tests are set to carry out standard error analysis.

[0045] Example 2

[0046] The copper sheet in step (2) of Example 1 was replaced with a Φ0.2×5 cm copper wire (the volume ratio of the copper wire to the volume of the acid solution was 0.16 cm 3 :200mL), and other parameters are the same as those in Example 1.

[0047] Comparative Example 1

[0048] The oxygen nanobubble solution in step (2) of Example 1 was replaced with ultrapure water, and the other parameters were the same as those in Example 1.

[0049] Comparative Example 2

[0050] The oxygen nanobubble solution in step (2) of Example 2 was replaced with ultrapure water, and the other parameters were the same as those of Example 2.

[0051] Comparative Example 3

[0052] The copper sheet in Example 1 is omitted, and other parameters are the same as those in Example 1.

[0053] Comparative Example 4

[0054] The pH value of the solution in step (2) of Example 1 was adjusted to 1.70, and the copper sheet in step (2) of Example 1 was omitted. Other parameters were the same as those in Example 1.

[0055] Comparative Example 5

[0056] The pH value of the solution in step (2) of Example 1 was adjusted to 1.10, and the copper sheet in step (2) of Example 1 was omitted. Other parameters were the same as those in Example 1.

[0057] Comparative Example 6

[0058] The pH value of the solution in step (2) of Example 1 was adjusted to 0.70, and the copper sheet in step (2) of Example 1 was omitted. Other parameters were the same as those in Example 1.

[0059] The oxygen nanobubble solution prepared in step (1) of Example 1 was photographed using a nanoparticle tracking analyzer, and the micrograph thereof is shown in FIG. Figure 1 As shown. Figure 1 Obvious white spots can be found in the image, which are oxygen nanobubbles.

[0060] The particle size distribution and concentration of oxygen nanobubbles in the oxygen nanobubble solution prepared in step (1) of Example 1 were characterized using a nanoparticle tracking analyzer. The distribution results of the concentration of oxygen nanobubbles along with their particle size are as follows: Figure 2 As shown. Figure 2 It can be seen that the average particle size of oxygen nanobubbles is about 266nm and the concentration is about 3×10 6 Particles / mL.

[0061] The free radical species generated by the oxygen nanobubbles prepared in step (1) of Example 1 were identified using an electron spin resonance spectrometer. Figure 3 As shown. Figure 3 As can be seen, the ESR spectrum has 4 different peaks with peak heights of 1:2:2:1, and its hyperfine splitting constant is A N =A H =14.9G, which is a typical ESR parameter of DMPO-OH, which proves the existence of hydroxyl radicals in the oxygen nanobubble solution.

[0062] The oxidation effect of oxygen nanobubbles on divalent iron under different pH conditions was tested in Comparative Examples 3 to 6. Figure 4 As shown. Figure 4It can be seen that the oxidation rate of divalent iron decreases with the increase of pH value. When the pH value is 0.40, the oxidation rate of divalent iron is the highest at 16.5%.

[0063] The oxidation effect of oxygen nanobubbles on divalent iron was tested under different catalyst conditions in Examples 1 to 2, and Comparative Example 3 was used as a control group without a catalyst. The results are as follows: Figure 5 As shown. Figure 5 It can be seen that in the presence of a catalyst, the oxidation rate of ferrous iron continues to increase over time, and the oxidation rate is fastest within the first 4 hours of the reaction. The catalytic oxidation effect of the copper sheet is better than that of the copper wire, and the oxidation rate after 24 hours is 88.51%. Compared with the group without a catalyst, the oxidation rate of ferrous iron has been significantly improved.

[0064] The morphology of the copper sheet in Example 1, the copper sheet after 24 hours of oxidation reaction in Comparative Example 1, and the copper sheet after 24 hours of oxidation reaction in Example 1 were characterized by scanning electron microscopy. The SEM results are as follows: Figures 6 to 8 The morphology of the copper wire in Example 2, the copper sheet after 24 hours of oxidation reaction in Comparative Example 2, and the copper sheet after 24 hours of oxidation reaction in Example 2 were characterized by scanning electron microscopy. The SEM results are shown in Figures 9-11 As shown. Figures 6 to 11 It can be seen that the copper sheet and copper wire are corroded to varying degrees after 24 hours of oxidation reaction. Under the same pH conditions, the degree of corrosion in the oxygen nanobubble solution is more obvious than that in ultrapure water.

[0065] The copper sheet of Example 1 and the copper wire of Example 2 were subjected to elemental analysis by energy dispersive spectrometer after oxidation for 24 hours. The EDS results were as follows: Figures 12-13 As shown. Figures 12-13 It can be seen that no iron element was detected on the surface of the copper wire and the copper sheet, which indicates that the decrease in the concentration of divalent iron during the reaction is not caused by adsorption on the surface of the solid catalyst, but because the divalent iron is oxidized to trivalent iron by oxygen nanobubbles.

[0066] It can be seen from the above embodiments and comparative examples that, when copper is added as a catalyst when the oxygen nanobubble solution oxidizes divalent iron ions under acidic conditions, the oxidation performance of the oxygen nanobubbles on divalent iron ions is significantly improved.

[0067] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements without departing from the principle of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for oxidizing divalent iron ions using oxygen nanobubbles, comprising the following steps: (1) preparing an oxygen nanobubble solution; The method for preparing the oxygen nano bubble solution comprises: preparing the oxygen nano bubble solution by using a circulating water power nano bubble generator; When the volume of the solution is 5 to 7 L, the pressure value when preparing the oxygen nanobubble solution is 4 to 6 bar; The time for preparing the oxygen nanobubble solution is 4 to 6 minutes; (2) catalytically oxidizing divalent iron ions in the oxygen nanobubble solution obtained in step (1) using copper as a catalyst under acidic conditions; the pH value of the solution under acidic conditions in step (2) is 0.40 to 1.76; the copper in step (2) is copper wire or copper sheet; and the temperature of the catalytic oxidation is 25 to 35°C.

2. The method according to claim 1, characterized in that The acid in the acidic condition of step (2) is one or more of sulfuric acid and hydrochloric acid.

Citation Information

Patent Citations

  • Method for strengthening iron removal by oxygen oxidation in solution by using microbubble generating device

    CN111663040A

  • A process of preparing ferric sulfate solution

    EP0316487A1